Reorientation of Indonesian Criminal Law Politics: Shifting Paradigm from Retributive to Restorative in Death Penalty Regulation - Rivanie, Syarif Saddam; Ashar, M. Susilo Ihlasul (CV. Social Politic Genius (SIGn), 2025)
The shift in global sentencing paradigms, which increasingly abandons the retributive approach in favor of human rights protection, creates an internal normative antinomy within the Indonesian legal system. This antinomy occurs between the constitutional guarantee of the right to life and the continued existence of the death penalty. This study aims to develop a model for reorienting national penal policy from a retributive to a restorative paradigm. Furthermore, this study analyzes the juridical mechanism for implementing the conditional death penalty following the enactment of Law Number 1 of 2023. This research constitutes normative legal research employing statute, case, and conceptual approaches. The legal materials analyzed include primary sources, such as statutory regulations and Constitutional Court decisions, as well as secondary sources from the literature and international reports. The results indicate that the alteration of the death penalty status from a principal punishment to a special punishment with a 10 (ten) year probationary period constitutes a transitional or quasi-abolitionist compromise. This compromise aims to bridge global demands and domestic social defense needs. However, the vacuum of norms regarding the assessment indicators for “commendable attitude” during the probationary period has the potential to cause legal uncertainty. Therefore, integrating restorative justice principles through the recovery of state losses (for corruption) and contributions to severing criminal chains (for narcotics) becomes an imperative objective parameter for sentence alteration. This study concludes that the probationary mechanism must be interpreted as a measurable momentum of rehabilitation, not merely as a postponement of execution. It requires technical implementing regulations in the form of Government Regulations and Supreme Court Regulations.